(untitled) (Heritage, 2023)
Today’s foreign language teaching increasingly involves the daily use of new technologies and the development of digital literacy of both teachers and students. With the goal of realizing pedagogical work in a digital environment, there are also needs for new approaches and learning. In this regard, among modern approaches, multimodality and the use of modes in the creation of teaching materials stand out. Namely, multimodality is a phenomenon of communication that includes semiotic resources or modes such as text, photos, videos, audio recordings, graphs, colors, illustrations, gestures. Bearing in mind what multimodality in teaching entails, it is not surprising that some teachers choose active and creative use of modes when create didactic materials in a digital environment. Despite the fact that the topic of teaching Serbian as a foreign language is becoming more prevalent, both in practice and in scientific literature, the need for teaching materials in a virtual environment is still present. Therefore, some authors, more precisely, teachers of the Serbian language as a foreign language, who choose an online environment for their teaching work, happily decide to use numerous modes in creating online language courses because they make teaching interesting and visually attractive for members of another nation. For this reason, the goal of this paper is to point out the existence and importance of multimodality and modes in online teaching of Serbian as a foreign language, based on the collected scientific works that deal with the mentioned topic.